2002
DOI: 10.1016/s1044-0305(02)00389-6
|View full text |Cite
|
Sign up to set email alerts
|

An atmospheric pressure ion lens that improves nebulizer assisted electrospray ion sources

Abstract: An atmospheric pressure ion lens improves the performance and ease of use of a nebulizer assisted electrospray (ion spray) ion source. The lens is comprised of an oblong-shaped stainless steel ring attached to an external high voltage power supply. The lens is located near the tip of the conductive sprayer, and is maintained at a potential less than that of the sprayer. The ion lens improves the shape of the equipotential lines in the vicinity of the sprayer tip. This lens gives approximately a 2-fold reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…Modifications in ESI source design mainly involve the number and the positioning of heated gas inlets, the sprayer orientation relative to sampling orifice as well as the diameter of MS orifice or the number of transfer capillaries . Further, the ion lens system may be a starting point for improvements in ESI design as it decides on ion sampling efficiency and stability of ion signals …”
Section: Introductionmentioning
confidence: 99%
“…Modifications in ESI source design mainly involve the number and the positioning of heated gas inlets, the sprayer orientation relative to sampling orifice as well as the diameter of MS orifice or the number of transfer capillaries . Further, the ion lens system may be a starting point for improvements in ESI design as it decides on ion sampling efficiency and stability of ion signals …”
Section: Introductionmentioning
confidence: 99%
“…These efforts have resulted in significant gains in sensitivity, but design optimization efforts have generally reached the point of diminishing returns; e.g., our experience indicates that the ESI interfaces on instruments obtained from different vendors now provide similar levels of performance. This situation persists despite aggressive efforts aimed at increasing ion transmission from the ESI emitter to the capillary inlet, e.g., by means that include a Venturi device [7][8][9] and electrostatic lenses [12][13][14][15]. An electrodynamic ion funnel interface [16 -18] developed earlier in our laboratory was designed to overcome ion losses due to the small aperture of the skimmer [6] by allowing all ions that exit the inlet capillary to be efficiently captured and transmitted into the next vacuum stage.…”
mentioning
confidence: 99%
“…A previously described home‐built ion spray source15 was used. The sprayer tip was positioned 15 mm from the curtain plate, and the orientation of the sprayer capillary was 60° with respect to the curtain plate (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work by our group14, 15 has demonstrated that an oblong‐shaped atmospheric pressure ion lens improves the performance of ESI sources at flow rates from 0.2 to 5 µL/min. Thompson and coworkers16 also reported that a hemispherically shaped electrostatic lens at atmospheric pressure was able to compress the space‐charge in nano‐ESI and increase the average current density in the plume by a factor of 3.…”
mentioning
confidence: 97%